Legal Education and access to legal professions in Spain - Salvador Coderch, Pablo (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
In Spain, legal education is organised as 4 years long undergratuate study which in 62 different law schools (on top of the distance learning schools). Law is still a university education by default of sorts. Access to the most relevant legal professions requires overcoming different competition models, traditionally called «oposiciones», after years of preparation. Access to the bar requires a master course followed by a not extremely difficult exam. In this century, many students combine simultaneous studies of law and economy, but evolving to a postgraduate law schooling system would further improve the legal education.